A Census of WISE-selected Dual and Offset AGNs Across the Sky: New Constraints on Merger-driven Triggering of Obscured AGNs - R. Scott Barrows; Julia M. Comerford; Daniel Stern; Roberto J. Assef (The Astrophysical Journal, 2023)
Pairs of galaxies hosting active galactic nuclei (AGNs) are powerful probes of merger-driven supermassive black hole (SMBH) growth as they can resolve individual AGNs and trace mergers over a large range of physical separations. To exploit this on a large scale for the first time for both obscured and unobscured AGNs, we use the photometric redshifts of AGNs selected by the Wide-field Infrared Survey Explorer (WISE) to find probabilistic pairs (<100 kpc separations) across the sky, along with a comparison sample of inactive galaxy pairs. Our final sample of integrated pair probabilities yields 198 AGN–AGN pairs (dual AGNs) and 2767 AGN–galaxy pairs (offset AGNs) with uniformly measured AGN and host galaxy physical properties. We find the fraction of galaxy pairs hosting WISE AGNs is dominated by offset AGNs and is significantly elevated above that of inactive galaxies for large host stellar masses. We show how the AGN merger fraction directly increases with AGN extinction for both offset and dual AGNs, with up to ∼40% of heavily obscured AGNs found in galaxy pairs. Elevated AGN merger fractions coincide with increased host specific star formation rates that suggest merger-driven coevolution of galaxies and SMBHs. Among dual AGNs, the most rapid SMBH growth may occur within the less-massive galaxy. Relative to stochastic mechanisms, mergers produce an excess of AGNs at increasingly smaller separations, especially for obscured AGNs (up to a factor of ∼5), and are augmented by correlated triggering. Finally, this excess is stronger than for lower-luminosity optically selected AGNs, regardless of the AGN obscuration level.